The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques